The Influence of Perceived Organizational Support and Proactive Personality on Employee Engagement for University Lecturers: The Mediating Role of Self-Efficacy - Rungruang, Siriwut; Suwanragsa, Issara (Business Administration and Management Journal Review, 2021)
The purpose of this paper is to investigate the influence of perceived organizational support (i.e. organization climate, peer support, and supervisor support) and proactive personality on employee engagement. It is hypothesized that the influence of perceived organizational support and proactive personality on employee engagement is not direct. However, it is mediated by self-efficacy. Using a quantitative analysis method, data were collected with questionnaires distributed to 401 university lecturers from both public and private universities in Thailand. The results revealed that perceived organizational support and proactive personality influenced employee engagement. However, the mediating role of self-efficacy on the relationships between perceived organizational support and proactive personality and employee engagement was not significant. The research has implications for lecturer recruitment. Particular behaviors in regard to both groups and supervisors, such as having a proactive personality, focusing on sharing, discussing related problems, and caring about others’ well-being and value, were found to enhance employee engagement.